SOCIOLOGICAL INTERPRETATION BY RELIGIOUS COURT JUDGES: Views of Bantul Religious Court Judges on the Husband's Financial Capability Requirement for Polygamy - Syahrin, Alfi; Sodiqin, Ali; Hakimi, Abdul Rahim (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2022)
The legal substance in the Government Regulation on Marriage Law Implementation, particularly on financial requirements for polygamy, allows the emergence of ambiguous interpretations for judges. Article 41, paragraph C, of that regulation, does not specify how judges should assess the financial strength of a husband who intends to engage in a polygamous marriage. Likewise, the Bantul Religious Court judges (who granted the most polygamy permits in Yogyakarta of 2021) have a different perspective on the requirements for financial ability in polygamy. In this context, this study examines how Bantul Religious Court judges deal with this legal ambiguity in their decisions. This study examines 14 polygamy verdicts. This research finds that the concept of financial ability in the polygamy case is the judge's way of measuring the justice of the husband. Justice primarily refers to the husband's capability to provide an adequate financial portion of the fair share to their wife (in the future). To know the husband's financial ability, judges apply a holistic approach that rests on a sociological lens.[Substansi hukum dalam Peraturan Pemerintah tentang Pelaksanaan Undang-Undang Perkawinan, khususnya tentang persyaratan keuangan untuk poligami, memungkinkan munculnya penafsiran ganda bagi hakim. Pasal 41 huruf C peraturan itu tidak mengatur bagaimana seharusnya hakim menilai kekuatan keuangan seorang suami yang hendak melakukan perkawinan poligami. Begitu pula dengan Hakim Pengadilan Agama Bantul (yang paling banyak memberikan izin poligami di DIY tahun 2021) memiliki pandangan yang berbeda tentang syarat kemampuan finansial dalam poligami. Dalam konteks tersebut, penelitian ini mengkaji bagaimana Hakim Pengadilan Agama Bantul menyikapi ambiguitas hukum tersebut dalam putusannya. Studi ini mengkaji 14 vonis poligami. Penelitian ini menemukan bahwa konsep kemampuan finansial dalam kasus poligami merupakan cara hakim mengukur keadilan suami. Keadilan terutama mengacu pada kemampuan suami untuk memberikan porsi keuangan yang memadai dari bagian yang adil kepada istri mereka (di masa depan). Untuk mengetahui kemampuan finansial suami, hakim menerapkan pendekatan holistik yang berpijak pada lensa sosiologis.]